The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/1744-7917.12347
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer activity ofHelitroninsericin-1gene promoter fromBombyx mori

Abstract: Sericin is a kind of water-soluble protein expressed specifically in the middle silk gland of Bombyx mori. When the sericin-1 gene promoter was cloned and a transgenic vector was constructed to express a foreign protein, a specific Helitron, Bmhel-8, was identified in the sericin-1 gene promoter sequence in some genotypes of Bombyx mori and Bombyx mandarina. Given that the Bmhel-8 Helitron transposon was present only in some genotypes, it could be the source of allelic variation in the sericin-1 promoter. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Indeed, we observed that Helitrons represent 50% of all cases. These elements have been extensively reported on promoter regions of other eukaryotic species (102)(103)(104)(105), in which a few cases of embedded TFBSs were reported (106,107). Here, we demonstrated that part of the enrichment in TEs observed at the promoter region of ORs might be due to the exaptation of TFBSs mostly derived from Helitrons.…”
Section: Or Genes Are Enriched With Te Insertions At 2 Kb Upstream Re...supporting
confidence: 57%
See 1 more Smart Citation
“…Indeed, we observed that Helitrons represent 50% of all cases. These elements have been extensively reported on promoter regions of other eukaryotic species (102)(103)(104)(105), in which a few cases of embedded TFBSs were reported (106,107). Here, we demonstrated that part of the enrichment in TEs observed at the promoter region of ORs might be due to the exaptation of TFBSs mostly derived from Helitrons.…”
Section: Or Genes Are Enriched With Te Insertions At 2 Kb Upstream Re...supporting
confidence: 57%
“…Helitrons have been extensively reported as a source of TFBSs when located at the promoter region of genes. In the bat Myotis lucifugus , 1.4% of the transcripts from the salivary gland have Helitron -derived sequences, for which ∼6% correspond to promoters (103). In the plant Brassica napus , an Helitron insertion disrupts the ancestral promoter of the gene BnSP11-1 , altering the mating system of the populations carrying this insertion, which in turn contributes to the adaptation and speciation (119).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al . cloned a specific helitron, Bmhel‐8, from the sericin‐1 gene promoter sequence and showed that Bmhel‐8 exhibits enhancer activity in a sericin‐1 promoter‐driven gene expression system, but does not influence tissue‐specific expression of sericin‐1 (Huang et al ., ). Lu et al .…”
mentioning
confidence: 97%